PERBANDINGAN SISTEM KEPARTAIAN DAN KAITANNYA DALAM PEMILIHAN PRESIDEN DI INDONESIA DAN FILIPINA: Comparison Of Participation Systems And Its Relationships In Presidential Elections In Indonesia And Philippines - Darmansyah, Irawan Ro; Sulistyowati, Tri (AMICUS CURIAE, 2024)
The emergence of political parties in a country can determine its political system. Each democratic countries has its own way to elaborate their peoples right to vote and to elaborate any political parties to carry their strong member as President and Vice President in an election. This research used normative juridical research and comparative method where the conclusion were drawn using deductive method. In this research, two democratic country will be compared. Indonesia and Philippines has many similarities trough the differences in their political party system related to presidential election. Multi party system is used in both countries. There are similarities in the form of implementation of voting rights, nominating candidates through political parties, and nominating parties as election participants. Therefore the difference is known in the authority of the election commission, presidency period, the threshold for presidential nomination, the election round system, the vote counting mechanism, and the voting system. This differences and similarities generate values that can be developed such as general conditions for the establishment of political parties, the presidential thresholds, and utilize a vote counting machines to calculate the results of vote recapitulation.